Regulation of groE expression in Bacillus subtilis: the involvement of the sigma A-like promoter and the roles of the inverted repeat sequence (CIRCE). - Yuan, G (1995)
To study the regulatory mechanism controlling the heat-inducible expression of Bacillus subtilis groE, two regulatory elements, the sigma A-like promoter and the inverted repeat (IR [CIRCE]) in the control region, were characterized. The groE promoter was shown to be transcribed by the major RNA polymerase under both heat shock and non-heat shock conditions. The IR was found to have two functions. (i) It ensures the fast turnover of the groE transcript, and (ii) it serves as an operator. This IR acts as a negative heat shock regulatory element, since deletion of this sequence resulted in high-level expression of groE even at 37 degrees C. Although this IR is present in the 5' untranslated region of the groE transcript, groE transcripts under heat shock and non-heat shock conditions showed similar in vivo half-lives of 5 min. This rapid turnover at 37 degrees C requires the presence of the IR. Without the IR, the groE transcript showed a longer half-life of 17 min. Increasing the distance between the groE transcription start site and the IR systematically by inserting nucleotide sequences from 5 to 21 bp in length resulted in a gradual abolition of the negative regulatory effect mediated by the IR. This effect was not due to a significant change in transcript stability or the transcription start site and is consistent with the model that this IR serves as an operator.